2008
DOI: 10.1021/jp077376k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Accuracy of Density Functionals for Prediction of Relative Energies and Geometries of Low-Lying Isomers of Water Hexamers

Abstract: Water hexamers provide a critical testing ground for validating potential energy surface predictions because they contain structural motifs not present in smaller clusters. We tested the ability of 11 density functionals (four of which are local and seven of which are nonlocal) to accurately predict the relative energies of a series of low-lying water hexamers, relative to the CCSD(T)/aug′-cc-pVTZ level of theory, where CCSD(T) denotes coupled cluster theory with an interative treatment of single and double ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
185
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(203 citation statements)
references
References 67 publications
15
185
3
Order By: Relevance
“…3 is self-contained, i.e., was obtained completely within the given approach (except for the benchmark results which were computed at geometries optimized in smaller bases and not including the δE CCSD(T) int contribution). Figure 3 shows that the interaction energies from CCpol23+ and both benchmarks are very close in all cases, although CCpol23+ is noticeably closer to the CBS-level benchmarks of Bates and Tschumper 71 (0.01-0.03 kcal/mol) than to the haTZ results of Dahlke et al 66 (0.03-0.06 kcal/ mol). This is not accidental, as both the two-body and the three-body parts of CCpol23+ were fitted to energies obtained with basis sets much larger than haTZ.…”
Section: B Water Hexamermentioning
confidence: 78%
See 3 more Smart Citations
“…3 is self-contained, i.e., was obtained completely within the given approach (except for the benchmark results which were computed at geometries optimized in smaller bases and not including the δE CCSD(T) int contribution). Figure 3 shows that the interaction energies from CCpol23+ and both benchmarks are very close in all cases, although CCpol23+ is noticeably closer to the CBS-level benchmarks of Bates and Tschumper 71 (0.01-0.03 kcal/mol) than to the haTZ results of Dahlke et al 66 (0.03-0.06 kcal/ mol). This is not accidental, as both the two-body and the three-body parts of CCpol23+ were fitted to energies obtained with basis sets much larger than haTZ.…”
Section: B Water Hexamermentioning
confidence: 78%
“…First, we optimized the geometries of the cage, prism, book, boat, bag, and ring isomers using the CCpol-8s+NB potential, starting from the configurations taken from Ref. 66. Since the latter configurations included flexible monomers, we "projected" our monomers similarly as in the case of the TIP5P potential, except that our rigid-monomer bisector now coincides with the line connecting the position of the oxygen atom with the midpoint of the segment connecting the two hydrogens.…”
Section: Choice Of Trimer Configurationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings indicated that the following interactions may be important in the potency of N-BPs: hydrogen bonding with Thr 201 and/or Lys 200, where a bifurcated bond is more potent than a single bond; CH-O hydrogen bonding with the backbone carbonyl oxygen atom of Phe 99; andinteraction with the sidechain of Phe 99. Truhlars group recently developed the global hybrid meta functionals M05-2X [5] and M06-2X [6] and demonstrated that these methods can be effectively applied to many problematic systems [7,8]. Here, we conducted quatum mechanical calculations for several BPs (minodronate, risedronate, alendronate) and their surrounding residues using the M06-2X method.…”
Section: Introductionmentioning
confidence: 99%